(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Microfinance has emerged as a much needed tool of socio-economic development particularly to the women in the developing economies. The existing study focuses on the prism of business economics to investigate the nature of interventions in a microfinance system to give women economic power as a performance of the enterprise, diversity of leadership, and digital interaction. According to the empirical models, the analysis measures the impact of a better access to credit and the proportion of women in executive and board roles on the level of firm financial returns and a composite Empowerment Impact Index (EII). The results show that there is statistically significant positive relation between gender-diverse leadership and corporate financial performance (ROE), and authenticity in digital engagement and empowers outcome. Nonetheless, the analysis also indicates that there are still significant challenges, such as the presence of socio-cultural barriers and digital disparities that moderately affect these positive effects.